2019
DOI: 10.11604/pamj.2019.32.154.18372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of neutrophil/lymphocyte ratio and platelet/lymphocyte ratio in recurrent epistaxis in childhood: case controlled study

Abstract: Introduction the aim of this study was to investigate the possible relationship of neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR) and routine hematological parameters with recurrent epistaxis in children. Methods İn this retrospective case-controlled study, 294 patients aged between 2 and 18 years who applied to the Tokat State Hopital Ear Nose Throat Clinic due to recurrent epistaxis between January 1 s t 2013 and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Zou et al reported that PLR was associated with gastrointestinal hemorrhage in patients with acute cerebral haemorrhage 19 . In an another study, the mean PLR value of the pediatric recurrent epistaxis group was statistically higher than the control group 20 . In the study carried out by Gayret et al, PLR of the patients with gastrointestinal bleeding were found to be significantly increased compared to those without bleeding 21 .…”
Section: Discussionmentioning
confidence: 79%
“…Zou et al reported that PLR was associated with gastrointestinal hemorrhage in patients with acute cerebral haemorrhage 19 . In an another study, the mean PLR value of the pediatric recurrent epistaxis group was statistically higher than the control group 20 . In the study carried out by Gayret et al, PLR of the patients with gastrointestinal bleeding were found to be significantly increased compared to those without bleeding 21 .…”
Section: Discussionmentioning
confidence: 79%